Komunikasi dan Kontroversi dalam Tradisi Tabuik di Kota Pariaman - Hafizah, Sucia; Chatra, Emeraldy; Arif, Ernita (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
The Tabuik tradition aims to commemorate the death of Husain bin Ali, the grandson of the Prophet Muhammad SAW carried out by the people of Pariaman City. Although the majority of Pariaman people are Sunni Muslims, this tradition continues to be preserved, symbolizes cultural identity, and combines elements of custom and religion. However, over time, the Tabuik celebration has also experienced changes and controversies, especially related to the differences in views between Tuo Tabuik, the government, and the community. This study aims to understand the dynamics of communication between traditional leaders, the community, and the government in the context of the Tabuik tradition. The research used a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The results showed that the debate between traditional leaders and the community regarding the indication of Shia Islam in this tradition showed a misunderstanding that needed to be resolved. Communication phenomena in the form of controversies that occur are debates between traditional leaders and the community, debates between traditional leaders and the Tourism Office.